Long-term engraftment of human natural T regulatory cells in NOD/SCID IL2rγc(null) mice by expression of human IL-2. - Sojan Abraham; Rajendra Pahwa; Chunting Ye; Jang-Gi Choi; Savita Pahwa; Shashidhar Jaggaiahgari; Ashwin Raut; Shuiping Chen; N Manjunath; Premlata Shankar (PLoS ONE, 2012)
Regulatory T cells are essential to maintain immune homeostasis and prevent autoimmunity. Therapy with in vitro expanded human nT(Regs) is being tested to prevent graft versus host disease, which is a major cause for morbidity and mortality associated with hematopoietic stem cell transplantation. Their usefulness in therapy will depend on their capacity to survive, migrate appropriately and retain suppressive activity when introduced into a transplant recipient. The lack of a suitable animal model for studying the in vivo reconstitutive capability of human nT(Regs) is a major impediment for investigating the behavior of adoptively transferred nT(Regs)in vivo. We show that injection of a plasmid encoding human IL-2 is necessary and sufficient for long term engraftment of in vitro expanded nT(Regs) in NOD-SCID IL2rγc(null) mice. We also demonstrate that these in vivo reconstituted T(Regs) traffic to different organs of the body and retain suppressive function. Finally, in an IL-2 accelerated GVHD model, we show that these in vivo reconstituted T(Regs) are capable of preventing severe xenogenic response of human PBMCs. Thus, this novel 'hu-T(Reg) mouse' model offers a pre-clinical platform to study the in vivo function and stability of human nT(Regs) and their ability to modulate autoimmune diseases and GVHD.